Impact of pulpectomy versus tooth extraction in children's oral health-related quality of life: A randomized clinical trial - Olegário da Costa, Isabel (My University, 2023)
Aim: The aim of this randomized clinical trial was to compare the impact of two management options for primary molars with pulp necrosis (pulpectomy or extraction) on children's oral health-related quality of life (OHRQoL). Design: A total of 100 children aged 3-5 years with at least one necrotic primary molar were selected and randomized into the study groups. The Brazilian version of early childhood oral health impact scale (B-ECOHIS) was completed by the parent proxy reports at baseline and after 4, 8 and 12 months. Differences between the trial groups were assessed through bootstrap linear regression for B-ECOHIS scores, logistic regression for dental pain self-reports and anxiety scores (α = 5%). Results: The mean (SD) B-ECOHIS scores at baseline and after 12 months were 17.7 (6.5) and 3.0 (4.0) in the pulpectomy group and 18.8 (7.7) and 7.9 (7.7) in the extraction group. Both treatments significantly improved OHRQoL, but tooth extraction group showed higher scores in total B-ECOHIS (p < .001) and most domains, indicating lower OHRQoL. Furthermore, higher anxiety levels were reported for dental extraction compared to pulpectomy (OR = 2.52; p = .008). Conclusion: Pulpectomy resulted in an improved OHRQoL scores after 12 months when compared to tooth extraction and should be considered as the treatment of choice for necrotic primary molars.
PUBLISHED
Keywords: Tooth extraction; Primary teeth; Anxiety; Children; Endodontic treatment; Pain; Patient-reported outcomes; Dentistry; Oral Diseases; Oral clinical research; Children